From Compliance to Co-Design: Transforming Accommodation Services at a Canadian College Through a People-Centred Service Design and Change Management Approach - Crowe, Sterling; Ghoneim, Anna (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2025)
This study explores the transformation of academic accommodation services at a Canadian post-secondary institution through the integration of service design, systems thinking, and critical disability theory in the people-centred systems change (PCSC) framework. Using a mixed-methods approach combining interviews, operational data, and co-design sprints the research examined how outdated, compliance-driven models can evolve into values-based, learner-centred systems. Key interventions included a tiered intake process, self-directed renewal options, and faculty development modules, resulting in reduced wait times, increased user satisfaction, and improved operational efficiency. Findings highlight how student experience can serve as a leverage point for systemic change and demonstrate that meaningful redesign is possible even within complex institutional environments. This case contributes to growing scholarship on equity-informed service innovation in higher education.